Strengthening the Role of Islamic-Based Family Mediation in Police Institutions: Lessons from BP4R in Indonesia for Global Practice - Saleh, Rusman Muhammad; Yetta, Yasin; Otta, Yusno Abdullah; Pedju, Rizaldy Purnomo (ANTMIND YOUTH EMPOWER FOUNDATION, 2025)
The increasing divorce rate among Polri personnel presents a critical challenge affecting individual well-being and institutional performance. As an advisory body within the Polri institution, the Badan Pembantu Penasehat Perkawinan, Perceraian, dan Rujuk (BP4R) is crucial in providing marital counseling and mediation services to support family stability. This study examines the effectiveness of BP4R in resolving family conflicts among Polri personnel through an Islamic law framework. Employing a qualitative approach with a descriptive-analytical design, data were collected through in-depth interviews, field observations, and document analysis at Polres Bolaang Mongondow Selatan. Findings indicate that BP4R's impact is constrained by limited training for its personnel, inadequate awareness among Polri members about its services, and cultural barriers that hinder open discussions about marital conflicts. To enhance BP4R’s role, this study proposes three key strategies: intensive training in Islamic law-based mediation, digitalization of counseling services, and multidisciplinary collaboration with religious leaders and psychologists. These recommendations aim to strengthen BP4R’s capacity to promote marital harmony, reduce divorce rates, and ensure Polri personnel's and their families well-being. The study contributes practical insights for institutional policy-making and theoretical perspectives on integrating Islamic law into family conflict resolution.